2020
DOI: 10.1140/epjc/s10052-020-7933-7
|View full text |Cite
|
Sign up to set email alerts
|

A universal framework for t-channel dark matter models

Abstract: We present the model implementation in FeynRules, which aims to offer a unique general framework allowing for all simulations relevant for simplified t-channel dark matter models at colliders and for the complementary cosmology calculations. We describe how to match next-to-leading-order QCD fixed-order calculations with parton showers to derive robust bounds and predictions in the context of LHC dark matter searches, and moreover validate two model restrictions (relevant for Dirac and Majorana fermionic dark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 94 publications
0
49
0
Order By: Relevance
“…Review on Dark Matter Tools Chiara Arina see [15][16][17][18][19]. From the same model Lagrangian, F R provides output files for computing collider predictions with MG5_ MC [20] (UFO format [21], the same used in M DM) and to apply collider bounds with the recasting tool M A 5 [22].…”
Section: Pos(tools2020)001mentioning
confidence: 99%
See 2 more Smart Citations
“…Review on Dark Matter Tools Chiara Arina see [15][16][17][18][19]. From the same model Lagrangian, F R provides output files for computing collider predictions with MG5_ MC [20] (UFO format [21], the same used in M DM) and to apply collider bounds with the recasting tool M A 5 [22].…”
Section: Pos(tools2020)001mentioning
confidence: 99%
“…For instance, in refs. [19,39] the discrepancies in the relic density calculation arise in the different treatment of the QCD sector in MG5_ MC and C H . In summary, in the standard WIMP freeze-out scenario, all public codes have been deeply tested and compared, process that has allowed to solve numerous bugs.…”
Section: Pos(tools2020)001mentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs via a t-channel interaction originating from an ST t operator. Many scalar DM models including a t-channel fermionic mediator have previously been studied [5][6][7][8][9][10][11], as top-philic DM models [12][13][14][15][16][17][18] and heavy DM with masses ranging up to several TeV have been discussed in the literature [19]. In particular, recent investigations [9,10] have shown that while leading order (LO) calculations allow for a heavy DM, next-to-leading-order (NLO) corrections to the annihilation cross section lead to significant modifications of the existing constraints on the model parameter space.…”
Section: Jhep07(2021)026mentioning
confidence: 99%
“…Figure11. Results of our fitting procedure for an example mass point featuring m S = 682.6 GeV, with varying r values (top row and bottom left figures), and the corresponding exponential fit to the deviation (bottom right).…”
mentioning
confidence: 99%